On the identity of Ashlockobius Slater & Slater and Villalobosothignus Brailovsky (Hemiptera: Heteroptera: Rhyparochromidae: Myodochini), with the description of a new arboreal species from Ecuador - Dellapé, Pablo Matías; Montemayor, Sara Itzel (Zootaxa, 2011)
The genus Villalobosothignus Brailovsky, 1984 is diagnosed, and Ashlockobius Slater & Slater, 1999 is synonymized with it. A new arboreal species of Villalobosothignus from Ecuador is described, and photographs of the adult and male genitalia are provided together with illustrations of certain diagnostic characters to facilitate identification.